Developing a framework for the design of the milling and rougher circuits for a platinum-bearing UG2 ore - Steyn, Johannes Jakobus (University of Cape Town, 2015)
Includes bibliographical references. === In the western limb of the Bushveld Igneous Complex, platinum is mined predominantly from two reefs – Merensky and UG2. Most of the platinum group minerals (PGM’s) in Merensky ore are associated with base metal sulphides (BMS), and thus Merensky concentrators will usually resemble simple BMS circuits. However, the mineralogy of UG2 ore is more complicated, and thus UG2 circuits are also more complex. The UG2 reef is a chromitite layer in the critical zone of the Bushveld Igneous Complex, which results in high chromite content. Chromite causes significant complications in the downstream smelter process, and therefore chromite constraints are imposed on UG2 concentrators. A further aspect complicating the treatment of UG2 ore is that PGM’s are not only associated with BMS, but ultra-fine PGM’s are also locked in gangue minerals. This affects the milling and flotation characteristics of the circuits, as it is not possible to efficiently target the liberation and recovery of relatively large BMS and ultra-fine PGM’s in the same circuit. As a result UG2 circuits have evolved to deal with these issues in a number of ways. This thesis focuses on the design of milling and flotation circuits to optimise the recovery of coarse BMS (with associated PGM’s) and ultra-fine PGM’s contained in associated siliceous gangue minerals. In order to achieve this, UG2 circuits usually feature more than one milling and flotation stage.